دffect of Organic Fertilization and Irrigation Level on Some Physical Prosperities of the Soil and Productivity of Maize( Zea maize L . )dctE (Journal of Hama University, 2024)
The research was carried out in five sites of the Syrian coast (Bahlouliya, Harisoun, Drakeish, Jebul, Kharayeb Salem) in the 2020-2021 agricultural season, with the aim of inventorying and characterizing wild oat Avena fatua L. types in these locations, and studying the phenotypic differences of each species in different locations. Where 30 oat plants were randomly identified within each of the five sites of different elevations above sea level for each type, and they were monitored at the stage of flowering and maturity, and studied using some morphological and chemical indicators.Two types of wild oats were monitored in all the studied sites, phenotypically different in the color of the lemma (dark and light),and Completely randomized design (C.R.D) was followed with three replications, as measurements were recorded: plant length (cm), number of inflorescences per plant, number of tillers per plant, leaf area (cm2), grain weight (g) content Leaves chlorophyll (µg/g) Wet weight, carotene content (µg/g) Wet weight. The linear correlation between the various studied traits were studied, as it was found that there was a high and significant correlation between grain weight and leaf area amounted to (0.79137) in wild oats with light-colored lemma The results of the study showed that the two types of wild oats studied in the lower area of sea level with a high spread and density. Where the sites of Harison (15.1g) and Bahlouliya (14.9g) were significantly superior to the rest of the sites in terms of grain weight and plant height (106.7cm) (150.7cm), and Kharayeb Salem (1189 µg/g) was significantly superior to the rest of the sites. In terms of leaf content of chlorophyll for wild oats with light lemma, as for wild oats with dark lemma, Jebul (15.8g) was significantly superior in terms of grain weight over the rest of the sites.